Exploring mathematical ideas in the ro’an tradition of an islamıc boarding school - Rosea Ajeng Prasastia Puri; Alifiani; Isbadar Nursit; Abdulaziz Hama (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
This study addresses a gap in ethnomathematics research by examining a pesantren cultural practice that has rarely been explored as a source of mathematical ideas. Previous ethnomathematics studies have mainly focused on traditional games, crafts, architecture, and visual motifs, while everyday communal practices in Islamic boarding schools (pesantren) remain underexamined. This study explores the ro’an tradition, a communal cleaning practice in an Islamic boarding school, to identify the mathematical reasoning embedded in its cultural routines and to consider its implications for mathematics education. Using an ethnographic design supported by observation, interviews, and documentation, the study analyzed six main aspects of ro’an: group formation, task assignment, workflow sequencing, scheduling, quantitative considerations, and rotational mechanisms. Data were interpreted through an ethnomathematics perspective and formalized carefully through ethnomodeling. The findings show that ro’an embodies various mathematical ideas, including set partitions, relations and functions, algorithms, proportional reasoning, spatial structuring, recurrence, and cyclic scheduling. These findings indicate that mathematical reasoning emerges naturally within pesantren cultural practices even without formal mathematical language. The study contributes to ethnomathematics by expanding its scope to religious-community practices and offers pedagogical implications for designing culturally responsive mathematics learning in pesantren and madrasah contexts.